The Implications of Sustainability Issues on Portfolio Choice and Asset Pricing - Shchepteva, Lilia; Zárybnická Žárová, Marcela, 1959-; Vítek, Leoš, 1970-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2021)
Sustainable investing is gaining on its importance since the awareness increase of its impact to the society and the environment. Sustainability incorporates the needs of today without limiting the ability to meet the needs of tomorrow. Press releases together with the company reports vastly impact stock prices and thus affect the investors’ preferences. The investors themselves also see the investing not only as the tool of maximizing profits, but in addition as an instrument to impact internal company polices and to create the difference to the world as a whole. Many had questioned the legitimacy of the social responsibility: incorporating sustainability aspect to investments decisions, despite bringing extra benefits, also results in unexpected costs. From this raised the dilemma, if the benefits of sustainable investment would outweigh its costs.
Vedoucí práce: Marcela Zárybnická Žárová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2021
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2021
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses